Left heart abnormalities in connective tissue disease patients with pre-capillary pulmonary hypertension as well as borderline mean pulmonary arterial pressure. Issue 5 (September 2015) - Tsuchida, Kosei; Yamada, Hidehiro; Yamasaki, Yoshioki; Suzuki, Kengo; Kongoji, Ken; Akashi, Yoshihiro; Ozaki, Shoichi
Abstract Objective. To describe co-existence of left heart abnormalities among case series of connective tissue disease (CTD) patients who showed pre-capillary pulmonary hypertension (PH) as well as borderline mean pulmonary arterial pressure (mPAP). Methods. From 2010 through 2012, 49 CTD patients suspected to have PH by exercise Doppler echocardiography underwent right heart catheterization. We retrospectively searched for left heart diseases from the available data on Doppler echocardiography, cardiac magnetic resonance imaging (MRI), scintigraphy, and endomyocardial biopsy. Results. Among 49 patients, 11 and 2 had pre- and post-capillary PH, respectively, and another 10 had borderline mPAP. Six of 11 patients with pre-capillary PH showed low pulmonary vascular resistance (PVR) (≤ 240 dynesseccm− 5) and low diastolic pulmonary gradient (< 7 mmHg). Seven of 10 patients with borderline mPAP had normal PVR (< 160) suggesting the presence of left heart abnormalities. Other abnormal findings included increased left atrial volume index and E/E' on Doppler echocardiography, delayed contrast enhancement by MRI, patchy area of hypoperfusion on thallium scintigraphy, and fibrosis in endomyocardial biopsy. Conclusion. The present case series suggested some contribution of left heart abnormalities to the increase in mPAP among CTD patients with pre-capillary PH as well as borderline mPAP.